2007
DOI: 10.1143/apex.1.011102
|View full text |Cite
|
Sign up to set email alerts
|

Continuous-Wave Operation of Blue Laser Diodes Based on Nonpolarm-Plane Gallium Nitride

Abstract: The continuous-wave (cw) operation of m-plane InGaN-based blue (460 nm) laser diodes (LDs) has been achieved. The threshold current and the corresponding threshold current density were 40 mA and 5.0 kA/cm2, respectively, with a 459 nm lasing wavelength under cw operation. The electroluminescence peak wavelength shift in pulsed mode was only 10 nm (58 meV), from spontaneous emission (at 0.3 mA) to stimulated emission (at 32 mA), which is extremely small when compared with that of c-plane blue LDs. This is first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
43
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 26 publications
4
43
0
Order By: Relevance
“…Therefore, further systematic studies will be required to clearly explain the origin of the different indium uptake on the two polar opposite planes. [17,18]. Figure 2 shows the dependence of the sub-threshold electroluminescence peak wavelength on current density for the (303 1) LD (published c-plane and m-plane devices are included for comparison) [17,18].…”
Section: Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, further systematic studies will be required to clearly explain the origin of the different indium uptake on the two polar opposite planes. [17,18]. Figure 2 shows the dependence of the sub-threshold electroluminescence peak wavelength on current density for the (303 1) LD (published c-plane and m-plane devices are included for comparison) [17,18].…”
Section: Results and Analysismentioning
confidence: 99%
“…[17,18]. Figure 2 shows the dependence of the sub-threshold electroluminescence peak wavelength on current density for the (303 1) LD (published c-plane and m-plane devices are included for comparison) [17,18]. In the 0.1 to 1 kA/cm 2 current density range, the blue-shift of the (303 1) LD is shown to be comparable to that of the m-plane LD emitting at 457 nm and much smaller than that of the cplane LD emitting at 470 nm.…”
Section: Results and Analysismentioning
confidence: 99%
“…This results in a displacement of electron and hole wavefunctions in quantum well structures leading to lower recombination efficiency and an emission wavelength shift with drive current [3]. Thus, the growth with other orientations such as (11-20) (a-plane) and (1-100) (m-plane) is a promising alternative for the development of highly efficient lasers and LED [4,5]. Recent studies have also indicated that such structures can incorporate higher Mg concentrations enabling increased p-type doping levels [6].…”
mentioning
confidence: 99%
“…Blue-violet and pure blue LDs on nonpolar (m-plane) substrates have already been fabricated [2][3][4][5]. However, there is a problem concerning their polarization properties.…”
mentioning
confidence: 99%
“…This stripe direction automatically requires using c-plane facets as cavity mirrors. Although the c-face mirrors were fabricated by cleavage or dry-etching techniques in the previous studies [2][3][4][5], we believe that m-face or a-face mirrors, satisfying the charge neutrality condition, can be formed much more easily by cleavage, and that high quality and low cost LDs can be realized using such easily cleaved facet mirrors. It has been theoretically proposed that the present undesirable polarization properties can be corrected using AlGaN substrates [6].…”
mentioning
confidence: 99%